Spinal cord infarction post cardiac arrest in STEMI: A potential complication of intra-aortic balloon pump use. (2nd January 2016) - Harris, Matthew; Karamasis, Grigoris V.; Chotai, Shayna; Tang, Kare H.; Clesham, Gerald J.; Kelly, Paul A.
Abstract : Intra-aortic balloon pump (IABP) is commonly used as a cardiac assist device in various clinical situations: cardiogenic shock, mechanical complications of acute myocardial infarction, high risk percutaneous coronary interventions, coronary artery bypass graft surgery and refractory unstable angina and ventricular arrhythmias as bridge to therapy. Although current data support its safety, there is limited or no support for its efficacy. We present the case of spinal cord infarction after IABP use in a patient who presented with ST elevation myocardial infarction and cardiac arrest and we discuss the potential mechanism of such a devastating complication.